Proses Interaksi Sosial Anak Autis di SLB - Warhandika, Fernanda Frisky; Azzahra, Aulia (Nur Science Institute, 2023)
Background: This study aims to determine the process of social interaction of autistic children at SLB Anugerah Colomadu. Method: This study uses a qualitative research method with a case study approach model. Data collection techniques through interviews and observation. The informant involved was the child's homeroom teacher. Result: The results of the study show that social interaction for autistic children can occur with teachers and peers. However, not all autistic children can interact with other people, because the majority of them are more interested in being alone by doing activities they like. Implication: The implications of this study are: First, the elementary schools' headmasters in Indonesia should enrich the teachers' knowledge and insight related to social interaction. Second, the government, supported by researchers, has to design an excellent assessment system to solve time limitations. Novelty: The present study revealed the implementation of social interaction especially autistic at elementary school comprehensively.